Genotyping and Phylogenetic Analysis of Plasmodium vivax Circumsporozoite Protein (PvCSP) Gene of Clinical Isolates in South-Eastern Iran - Soudabeh ETEMADI; Mehdi NATEGHPOUR; Afsaneh MOTEVALLI HAGHI; Hamid ESLAMI; Mehdi MOHEBALI; Neda SETAYESH; Aref TEIMOURI (Tehran University of Medical Sciences, 2020)
Background: Circumsporozoite protein (CSP) is one of the most important surface sporozoite antigens in malaria, recently considered as a candidate for vaccination. Considering the importance of CSP, this study was conducted to investigate the polymorphism and genetic diversity of Plasmodium vivax Circumsporozoite Protein (Pvcsp) in the southeastern region of Iran during 2015-2016. Methods: To investigate polymorphism and genetic diversity, 20 blood samples were collected from patients with P. vivax, then DNA was extracted and amplified using partial sequence of CSP gene. Polymerase chain reaction (PCR) products were sequenced and compared to sequences from genomic databases using BLAST. Genetic evaluation and phylogenic analysis were performed using MEGA7 and DnaSP5 software's on 38 sequences include 20 sequences of our study and 18 sequences of Gene Bank. Results: Eleven isolates were VK210 genotype and 9 isolates contained VK247. The result of variable segregation nucleotide site indicated that the differentiation of sequences in CSP were 25.67% in our 20 samples which are less than the 38 samples with a value of 26.67%. Comparing the ratio of dN/dS regions in the CSP gene indicates that the CSP varies more synonymously and amino acid has lower variation. Out of 38 samples, 35 unique haplotypes were identified based on 1042 nucleotide sequences in CSP, showing a variation percentage of 99.4%. Conclusion: The Tajima D analyses showed that CSP gene in P. vivax had a positive number in the total analyzed sequences, which means that the P. vivax mutations are in order to select positive evolution.